Incidental and Isolated Follicular Lymphoma In Situ and Mantle Cell Lymphoma In Situ Lack Clinical Significance. (July 2016) - Bermudez, Glenda; González de Villambrosía, Sonia; Martínez-López, Azahara; Batlle, Ana; Revert-Arce, José B.; Cereceda Company, Laura; Ortega Bezanilla, César; Piris, Miguel A.; Montes-Moreno, Santiago
Abstract : Follicular lymphoma in situ (FLIS) and mantle cell lymphoma in situ (MCLIS) are histopathologic findings of undetermined clinical significance. We studied a series of 341 consecutive lymph node resection specimens from patients diagnosed with colorectal (201 cases) and breast (140 cases) adenocarcinoma between 1998 and 2000. Incidental and isolated FLIS was identified in 11/341 patients (3.23%), whereas incidental and isolated MCLIS was found in 2/341 patients (0.59%). None of these cases developed overt lymphoma. A second series of 17 cases of FLIS (16 cases) and MCLIS (1 case) from consultation files was analyzed. Five cases with incidental and isolated FLIS were identified. None of these cases developed overt lymphoma. Overall, none of the 16 cases with incidental and isolated FLIS in both series developed overt FL after a median follow-up of 54 months (range, 7 to 187 mo). However, 12 of these cases with a clinical suspicion of lymphoproliferative disorder showed the association (in different lymph nodes) or combination (in the same sample) of FLIS or MCLIS with other lymphoid neoplasms (FL, splenic marginal zone lymphoma, nodal marginal zone lymphoma, Hodgkin lymphoma, diffuse large B-cell lymphoma, chronic lymphocytic leukemia/small lymphocytic lymphoma, multiple myeloma). In conclusion, the clinical relevance of FLIS and MCLIS seems to strictly depend on the clinical context. Incidental FLIS or MCLIS seem to have a very low risk for transformation, which recommends careful clinical examination after histopathologic diagnosis and conservative management with follow-up for a limited period of time. Abstract : Supplemental Digital Content is available in the text.